Spectral Studies of Co(II), Ni(II) and Cu(II) Complexes with 3-phenyl-2-thioquinazoline-4-(3H)-one, Semicarbazone and Thiosemicarbazone† - Rai, B.K. (Asian Journal of Chemistry, 2010)
A series of complexes of the type M(HL1)2 and [M(HL2-3)2X2], where M = Co(II), Ni(II) and Cu(II); HL1 = 3-phenyl-2-thioquinazoline-4-(3H)-one, HL2 = 3-phenyl-2-thioquinazoline-4-(3H) semicarbazone; HL3 = 3-phenyl-2-thioquinazoline-4-(3H) thiosemicarbazone; X = Cl– and Br–, have been synthesized and characterised by elemental analysis, molar conductivity, infrared spectra, electronic spectra and magnetic moment data. On the basis of experimental data the complexes of the type M(L1)2 are found to be square-planar whereas complexes of the type [M(HL2-3)2X2] are found to be octahedral. The complexes are found to be nonelectrolytic in nature on the basis of molar conductivity values.